Prospective clinical evaluation of 273 modified acid-etched dental implants: 1- to 5- year results - Michele De Franco; Francesco Guido Mangano; Alessandro Mangano; Andrea Pigato; Manuela Rapani; Giuseppe Luongo; Carlo Mangano (Ariesdue, 2012)
Aim: The aim of this study was to evaluate the implant survival and the implant-crown success of implants with surface treated with organic acids. Materials and methods: A total of 273 implants (Implus®, Leader-Novaxa, Milan, Italy) were inserted in 63 patients, from June 2006 to June 2010, in a single clinical centre. In each annual follow up session, clinical, radiographic and prosthetic parameters were evaluated. The implant-crown success criteria included the absence of pain, suppuration and clinical mobility, a distance between the implant shoulder and the first visible bone contact (DIB) <2.0 mm from the surgery and the absence of prosthetic complications at the implantabutment interface. Prosthetic restorations were 32 fixed partial prostheses, 48 single crowns and 16 fixed full arches. Results: The cumulative survival rate was 95.70% (93.81 maxilla, 98.24% mandible). Among the surviving implants, the implant-crown success was 96.07%. At the 5-year control, the mean DIB was 1.2 mm (± 0.5). Conclusion: Implants with surface treated with organic acids seem to represent a good solution for the prosthetic rehabilitation of partially and completely edentulous patients.